Della libertà dinanzi all’estinzione. La sostenibilità come questione morale e sociale - Pietropaoli, Matteo (Filosofia Morale/Moral Philosophy, 2024)
The aim of this work is to explore the relationship between the concept of freedom, particularly individual freedom in advanced societies, and the threat of extinction. The threat of extinction is not limited here to the extreme case of human life, but also includes the disappearance of natural ecosystems and animal species. This exploration highlights how the issue of sustainability, which is mainly of an environmental nature, requires moral and social (as well as scientific) considerations in order to be understood and addressed. In the case of studies relating to environmental ethics, in terms of sustainability, responsibility, and care for the environment, the interdisciplinary aspect must therefore be extended both to a sociological understanding of the current scenario and to a psychological reflection of ongoing dynamics. Once these aspects have been faced, starting from the primary character of individual freedom, this article tries to propose a moral experiment that recognizes the importance of the ethical theme of extinction, also in relation to the scientific uncertainty on the severity of the environmental disaster.